Visualization of the Implementation of Cross-Cultural Counseling in the “Serawai” Tribe Based on Multimedia - Sari, Widya Kartika; Ariani, Winda Ade; Jannah, Nurul; Afrianti, Vira; Pattisinai, Amanda Ristriana; Wildani, Zakiatul (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
Visualization of the application of cross-cultural counseling is a counseling approach that involves counselors and clients from different cultural backgrounds, where cultural information is presented explicitly. In this process, the potential for cultural prejudice is very high, so counselors must have cultural sensitivity to ensure the effectiveness of counseling services. Each client carries a self-development cycle influenced by the local wisdom of their culture, including in the context of the Serawai tribe culture, especially in the relationship between young people known as "berayak." This study focuses on applying multimedia-based cross-cultural counseling in the context of Serawai culture. Counselors use various media, such as PowerPoint presentations, videos, films, and other content relevant to clients' needs, to create a more inclusive and culturally responsive counseling environment. The use of multimedia not only helps in conveying counseling messages more clearly but also becomes a bridge between counselors and clients in understanding each other's cultural perspectives. The study results indicate that this approach effectively reduces barriers to cultural communication, increases client comfort, and deepens the client's self-reflection process. In addition, the use of multimedia strengthens the counselor's ability to accommodate cultural differences and helps clients understand counseling concepts through visualizations that are relevant to their culture. These findings provide new contributions to developing adaptive and contextual cross-cultural counseling models, especially in improving the quality of counseling services in areas with high cultural diversity.